2019
DOI: 10.1146/annurev-nutr-082018-124603
|View full text |Cite
|
Sign up to set email alerts
|

The Economics of Taxes on Sugar-Sweetened Beverages: A Review of the Effects on Prices, Sales, Cross-Border Shopping, and Consumption

Abstract: During the past decade, dozens of countries, regions, and cities have enacted taxes on sugar-sweetened beverages (SSBs). They have been primarily motivated by a desire to raise prices, reduce sales and consumption, improve population health, and raise revenue. This review outlines the economic rationale for SSB taxes and illustrates their predicted effects. It reviews the research on the effects of these taxes on retail prices, sales, cross-border shopping, consumption, and product availability. The evidence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
118
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(121 citation statements)
references
References 47 publications
3
118
0
Order By: Relevance
“…Therefore, all revenue estimates should be considered as upper bounds. Third, we also assumed that the taxes for the flat tax and for each tier were fully passed on to consumers, yet evidence from the USA reveals a range of tax pass-through from partial to over-shifting with heterogeneity by store type and beverage categories and sizes [28]. Further, no evidence exists on tax pass-through for discrete tiered taxes and one recent study on the South African HPL based on sugar content per gram showed that prices rose similarly for high-and low-sugar beverage products rather than linearly based on the tax design [21].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, all revenue estimates should be considered as upper bounds. Third, we also assumed that the taxes for the flat tax and for each tier were fully passed on to consumers, yet evidence from the USA reveals a range of tax pass-through from partial to over-shifting with heterogeneity by store type and beverage categories and sizes [28]. Further, no evidence exists on tax pass-through for discrete tiered taxes and one recent study on the South African HPL based on sugar content per gram showed that prices rose similarly for high-and low-sugar beverage products rather than linearly based on the tax design [21].…”
Section: Discussionmentioning
confidence: 99%
“…Despite increasing evidence of the potential impact of food policy interventions globally [15,19,21,[60][61][62], there is little locally speci c evidence and even less evidence about implementation processes for the Paci c. This project will strengthen the scaling up of interventions to improve diet in Fiji and Samoa.…”
Section: Discussionmentioning
confidence: 99%
“…Elasticity of supply (the expected proportional change in product supplied for a given percentage change in price) is shaped by the competitiveness of the local manufacturing and retail markets (Cawley et al 2019). Elasticity of demand (that is, the expected proportional change in product demand for a given percentage change in price) is shaped by a wide range of factors, including local preferences, incomes, advertising, availability of substitutions, and ease of cross-border shopping (avoiding the tax by shopping outside of the taxing jurisdiction) (Cawley et al 2019).…”
Section: Increasing Retail Pricesmentioning
confidence: 99%
“…• When demand is imperfectly elastic, sales can be expected to fall somewhat, but less than if demand was perfectly elastic (Cawley et al 2019).…”
Section: Box 2 Elasticities Of Supply and Demandmentioning
confidence: 99%